2015
DOI: 10.1155/2015/587193
|View full text |Cite
|
Sign up to set email alerts
|

TGFβSignaling in Tumor Initiation, Epithelial-to-Mesenchymal Transition, and Metastasis

Abstract: Retaining the delicate balance in cell signaling activity is a prerequisite for the maintenance of physiological tissue homeostasis. Transforming growth factor-beta (TGFβ) signaling is an essential pathway that plays crucial roles during embryonic development as well as in adult tissues. Aberrant TGFβ signaling activity regulates tumor progression in a cancer cell-autonomous or non-cell-autonomous fashion and these effects may be tumor suppressing or tumor promoting depending on the cellular context. The funda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
162
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(170 citation statements)
references
References 220 publications
(193 reference statements)
1
162
0
7
Order By: Relevance
“…For example, transforming growth factor b (TGFb) plays multifunctional roles in the regulation of cell behavior, and is implicated in both developmental biology and cancer biology. 20,21 TGFb is noteworthy for its paradoxical actions, having both inhibitory and stimulatory effects on cell growth. 22 In the early stages of cancer, TGFb acts as a growth inhibitor and tumor-suppressor; but in the later stages, it can act as a potent inducer of EMT.…”
Section: Inducers Of Emtmentioning
confidence: 99%
“…For example, transforming growth factor b (TGFb) plays multifunctional roles in the regulation of cell behavior, and is implicated in both developmental biology and cancer biology. 20,21 TGFb is noteworthy for its paradoxical actions, having both inhibitory and stimulatory effects on cell growth. 22 In the early stages of cancer, TGFb acts as a growth inhibitor and tumor-suppressor; but in the later stages, it can act as a potent inducer of EMT.…”
Section: Inducers Of Emtmentioning
confidence: 99%
“…TGF-β exists in at least three isoforms: TGF-β1, TGF-β2, and TGF-β3. [110] In the TGF-β superfamily, only TGF-β1, produced by activated microglia, and TGF-β2, produced by astrocytes and neurons. [111] TGF-β1 and TGF-β2 increased prominently after ischemic stroke.…”
Section: Il-1βmentioning
confidence: 99%
“…The transforming growth factor β (TGF-β) plays crucial roles in cell proliferation, differentiation, invasion, apoptosis, epithelial-mesenchymal transition (EMT), and metastasis in cancer cells [8]. And these functions mainly happen through TGF-β binding to 2 types of cell-surface transmembrane serine/threonine kinase receptors (TGF-β receptor types 1 and 2), and subsequent activation of SMAD-dependent and -independent signaling pathways [9].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of exogenous TGF-β reduces sensitivity to cisplatin in A549 cells, and inhibition of the TGF-β pathway restores confluence-dependent resistance to cisplatin in A549 cells [10], while the molecular mechanism of TGF-β-induced inhibition of sensitivity to cisplatin is still elusive. Accumulated evidences indicated that TGF-β stimulates various genes expression in lung fibroblast and epithelium during fibrogenesis [11], lung injury [12,] and tumorigenesis [8]. Among those genes, heat-shock protein 27 (HSP27), has been identified as an important regulator involved in the development of various cancers and chemoresistance during drug treatment [13,14,15].…”
Section: Introductionmentioning
confidence: 99%